Exploring bilingual first language acquisition: an ethnographic analysis of a bilingual child’s language development in a naturalistic setting - Whytsell, Andreia (Kansas State University, 2023)
This ethnographic study dissertation analyzes language development of a bilingual child in a naturalist setting in the United States. This research was conducted based on my personal and professional experience as an educational leader, a language teacher and a mother of a bilingual child. Through a qualitative method approach, including videos and audio recordings, I observed the child's linguistic abilities, social interactions, and the factors that influenced their language development, specifically how the language input impacts the output response. Results indicate that the quantity and quality of the input language impact the output response. Moreover, there was no evidence that there is a dominant language over the other. However, it is possible that one language might be stronger over the other when it comes to certain topics. There are language learning and acquisition strategies outlined in the last chapter that serve as a valuable resource for those invested in promoting and facilitating bilingualism in children. Overall, this study sheds light on the impact of the input to the output response in a bilingual child and contributes to understanding how language learning occurs in natural environments.
Keywords: Language development; Early language development; Bilingual first language acquisition; Bilingualism; Second language acquisition; Language learning